Angiosarcoma of the Scalp and Face: A Hard to Treat Tumor - Jmour Omar; Kochbati Lotfi; Ghith Sahar; Benna Farouk (Global Journal of Cancer Therapy - Peertechz Publications, 2017)
Cutaneous angiosarcoma is a rare and aggressive malignant tumor of vascular origin. Multimodality treatment including surgery, radiotherapy and chemotherapy should be used according to age and local spread. Prognosis is poor with a 5-year survival of 10-15%. We report the case of an angiosarcoma of the scalp and face treated with sequential contact radiotherapy and chemotherapy. After local response, the patient progressed in non-irradiated zone then had liver metastasis.